Analisis Semiotik dalam Syair Nandung Kesenian Masyarakat Kecamatan Peranap Kabupaten Indragiri Hulu - Kumala Sari, Endah; Rahayu, Sri (UIR PRESS, 2022)
Nandung is a song or poem that contains advice, trust, religious messages to be sung to children. Nandung in Peranap sub-district has become a tradition that has been passed down from generation to generation by mothers when putting their children to sleep, during bathing, akikah, and circumcision events. This research is motivated by several things, including the meaning contained in the poetry of the arts of the people of Peranap District, Indragiri Hulu Regency in semiotic studies. The problem that is taken in this research is how the semiotics contained in the nandung art poetry of the Peranap Subdistrict, Indragiri Hulu Regency, the theory used in this study is Pierce's theory which includes (1) icons, (2) indexes, (3) symbols. The approach used is a qualitative approach, the type of research used is field research. The method used is descriptive method, the technique used is hermeneutic technique. The result of this research is that there is a semiotic study of the aspects of icons, indices, and symbols in the Nandung Arts poetry of the Peranap sub-district community.